Pengaruh Inklusi Keuangan Terhadap Ketimpangan Distribusi Pendapatan Pada Negara Berkembang - Joan Marta; Shally Putri Amanda (Media Riset Ekonomi Pembangunan (MedREP), 2024)
The large income distribution inequality in developing countries indicates the high inequality that occurs. This study aims to analyze the effect of financial inclusion on income distribution inequality in 92 developing countries in 2010-2019. The dependent variable in this study is income distribution inequality and the independent variables consist of financial inclusion with indicators of the number of bank branches, the number of Automated Teller Machines (ATMs), and the proportion of bank loans to GDP. The control variables used in this study are Foreign Direct Investment, Trade Openness, Inflation, Labour, and Economic Growth. The analysis uses System Generalized Method of Moments (Sys-GMM) two-step estimator. The results show that access to financial services from bank branches and ATMs used has an effect on income distribution inequality, while the proportion of bank loans has no significant effect on income distribution inequality in developing countries